Repeated exposure to cocaine during adolescence enhances the rewarding threshold for cocaine‐conditioned place preference in adulthood. (28th January 2021) - Caffino, Lucia; Moro, Federico; Mottarlini, Francesca; Targa, Giorgia; Di Clemente, Angelo; Toia, Marianna; Orrù, Alessandro; Giannotti, Giuseppe; Fumagalli, Fabio; Cervo, Luigi
Abstract: Previous studies have shown that adolescent exposure to cocaine increases drug use in adulthood, albeit incubation of cocaine seeking was found to be attenuated in rats trained to self‐administer cocaine during adolescence. We here hypothesize that adolescent exposure to cocaine could alter the rewarding properties of the psychostimulant in adulthood. By employing two of the most widely used animal‐experimental‐preclinical models to investigate drug addiction, we evaluated whether contingent versus non‐contingent cocaine self‐administration during adolescence modulates its rewarding threshold in adulthood evaluated by conditioned place preference (CPP). Cocaine self‐administration during adolescence increases the rewarding threshold in adulthood; CPP for cocaine was observed at the higher (20 mg/kg), but not at the lower (10 mg/kg), dose employed. Rats exposed to either contingent or non‐contingent cocaine during adolescence exhibited the same behavior in the CPP paradigm suggesting that, under our experimental conditions, cocaine rewarding properties are shaped by the psychostimulant itself and not by its motivational effects. From a mechanistic standpoint, the preference for the 20 mg/kg cocaine‐paired side in a CPP paradigm appears to depend, at least partially, upon the formation of GluA2‐lacking Ca 2+ ‐permeable AMPA receptors and the consequent increase of αCaMKII activity in the NAc, both of which are instead reduced when the 10 mg/kg dose was used. In conclusion, contingent or non‐contingent cocaine exposure during adolescence desensitizes adult animals to a rewarding dose of cocaine (10 mg/kg) elevating the rewarding threshold necessary (20 mg/kg) to drive conditioned place preference, an effect that may predispose to higher consumption of cocaine during adulthood. Abstract : Cocaine self‐administration during adolescence increased the rewarding threshold necessary to drive conditioned place preference (CPP) in adulthood. It is hypothesized that increased formation of GluA2‐lacking Ca2 + −permeable AMPA receptors and increased activity of αCaMKII in the nucleus accumbens may contribute to induce CPP after exposure to cocaine self‐administration during adolescence.